Preparation method of silicon resin modified polyurethane-based intumescent flame-retardant heat-insulating coating

By introducing silicone resin into the polyurethane-based coating to form a dense carbon layer, the brittleness and malignant expansion of the polyurethane-based flame retardant coating are solved, and the anti-ablation and thermal insulation properties of the coating are improved, providing more Good thermal protection effect.

CN119192974APending Publication Date: 2024-12-27CIVIL AVIATION UNIV OF CHINA
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411547562.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The polyurethane-based flame retardant coating has problems such as low carbon production, large brittleness, severe melting droplets and large smoke production. The "malignant expansion" and "wick effect" of expandable graphite accelerate combustion, resulting in flame retardant and thermal insulation performance. insufficient.

Method used

By introducing silicone resin into the polyurethane-based coating, the amount of incorporation is regulated, and a thick and dense structure of porous carbon layer is formed, which inhibits the vicious expansion of expandable graphite, and realizes in-situ vitrification and ceramicization at high temperatures, thereby improving coating Anti-ablation and thermal insulation properties of the layer.

Benefits of technology

It significantly improves the ablation time and thermal insulation performance of the polyurethane-based expanded flame-retardant heat-insulating coating, extends the burn-through time of the carbon layer, enhances the adhesion and thermal protection effect of the coating, and effectively resists high-temperature flames. erosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192974A_ABST
    Figure CN119192974A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a silicon resin modified polyurethane-based intumescent flame-retardant heat-insulating coating, which comprises the following steps: mixing pure polyurethane and N, N-dimethylformamide according to a certain proportion, adding ammonium polyphosphate, pentaerythritol, melamine and expansible graphite, and uniformly stirring to prepare a polyurethane-based coating containing an intumescent flame-retardant system. And then adding silicon resin sol obtained by dissolving powdery methylsiloxane resin in isopropanol according to a ratio and uniformly stirring to modify. The preparation method has the advantages that the preparation process is easy to operate, green and free of pollution, renewable materials are used as raw materials, and the requirements for environmental protection and sustainable development are met; through the modification of the silicon resin, the malignant expansion of the expandable graphite is inhibited; the coating is well bonded with a base material, a carbon layer formed at a high temperature has excellent heat insulation performance and can well protect the base material, and the temperature of the back surface of the base material coated with the coating is only 174 DEG C under butane flame of about 1200 DEG C; the formed carbon layer has better stability under a high-temperature condition, and the burn-through resistance time exceeds 2 hours; according to the present invention, the formed thick, compact and porous carbon layer inhibits the generation of smoke, the heat release rate peak value of the coating is 183 KW / m < 2 >, the smoke release rate peak value is only 0.00147 m < 2 > / s, and the CO generation rate peak value and the CO2 generation rate peak value are respectively 0.00229 g / s and 0.1009 g / s.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flame retardant heat insulation coatings, and particularly relates to a method for preparing a silicone resin modified polyurethane-based intumescent flame retardant insulation coating. Background Art

[0002] Polyurethane (PU) coating is a new, high-grade and durable synthetic resin coating. It is mainly used in the fields of automobiles, electronics, aerospace, etc. due to its excellent adhesion, water and corrosion resistance, decorative and wear resistance. However, as an organic polymer material, polyurethane has a limiting oxygen index of only about 18%, is flammable in the air, and produces a large amount of toxic gases during combustion, such as CO, HCN, NO x Etc., which brings great fire hazards. Therefore, in order to protect the safety of life and property, polyurethane coatings need to be flame retardant modified.

[0003] The traditional polyurethane-based flame retardant coating of the APP-PER-MEL system has problems such as low carbonization, large brittleness, severe droplets and large smoke generation. Expandable graphite (EG) is an environmentally friendly intumescent flame retardant. At high temperatures, EG expands 150-300 times in volume, and the resulting "worm-like" carbon residue covers the surface of the porous carbon layer, serving as a barrier for heat and oxygen transfer. In addition, some non-combustible gases (CO2, H2O) produced during the expansion reaction dilute the mixture of O2 and fuel. Therefore, EG, as an additive, improves the flame retardant and heat insulation properties of polyurethane-based flame retardant and heat insulation coatings. However, EG has the following two effects as a flame retardant. The first is the "popcorn effect", which makes the loose or fluffy structure of the "worm-like" carbon layer easily blown away by the turbulence of the flame impact, resulting in a discontinuous and non-compact base left behind. The second is the "wick effect", which forms a continuous channel for flame propagation due to the presence of combustible impurities, thereby accelerating combustion. Therefore, it is urgent to modify the polyurethane-based flame retardant coating under this component to inhibit the "malignant expansion" of expandable graphite.

[0004] Silicone resin is a polymer network polymer with Si-O-Si as the main chain and other organic groups attached to silicon atoms. Due to the coexistence of organic and inorganic structures in its structure, it has good chemical corrosion resistance, electrical insulation and chemical stability. At the same time, the significant difference in the electronegativity of Si and O atoms in silicone resin makes it have a higher Si-O bond binding energy, which is difficult to break at high temperatures and can withstand temperatures above 1000°C. Therefore, using silicone resin as a modifier to further improve the flame retardant and thermal insulation properties of polyurethane-based flame retardant and thermal insulation coatings has important application value.

[0005] In order to solve the problems that the polyurethane-based flame retardant coating of the APP-PER-MEL-EG system has a short anti-ablation time and expandable graphite has "malignant expansion", the present invention uses silicone resin to modify the polyurethane-based flame retardant coating, adjusts the amount of silicone resin added, and optimizes and determines the coating formula and its preparation method based on improving the flame retardant and heat-insulating properties of the coating. Summary of the invention

[0006] In order to achieve the above object, the purpose of the present invention is to provide a method for preparing a silicone resin modified polyurethane based intumescent flame retardant thermal insulation coating.

[0007] To achieve the above object, the present invention provides the following technical solution: a method for preparing a silicone resin modified polyurethane-based intumescent flame retardant thermal insulation coating, specifically comprising the following steps:

[0008] The technical solution of this project is as follows:

[0009] (1) Put the polyurethane slurry in a container, then drop N,N-dimethylformamide (DMF) into the container and mix with the polyurethane (the mass ratio of DMF to polyurethane is 0.7-1.1:1.8-2.2), and mechanically stir at room temperature at a speed of 250-350 r / min for 10-15 minutes to prepare the coating matrix slurry.

[0010] (2) Weigh ammonium polyphosphate (APP), pentaerythritol (PER), melamine (MEL), expandable graphite (EG) and the slurry prepared in step (1) in order according to the mass ratio of 3.2-3.4:1.2-1.4:1.9-2.1:2.4-2.6:23.1-23.3, and place them separately. First, grind APP, PER, and MEL in a mortar, and add them to the slurry together with EG after they are completely ground and uniformly, and mechanically stir them at a speed of 250-350r / min at room temperature for 15-20min to obtain a mixed solution containing an intumescent flame retardant system.

[0011] (3) dissolving powdered methylsilicone resin in isopropyl alcohol (IPA) in proportion (the mass ratio of methylsilicone resin to IPA is 2.8-3.2:4.8-5.2), and mechanically stirring at room temperature at a speed of 250-350 r / min for 3-4 hours to obtain a transparent and viscous silicone resin sol.

[0012] (4) Add the silicone resin sol in step (3) to the mixed solution in step (2) (the mass ratio of silicone resin sol to mixed solution is 3.2-3.4:32.2-32.4), and mechanically stir at a speed of 250-350 r / min for 15-20 min at room temperature to obtain a slurry containing silicone resin. Then, add 101C type curing agent (the mass ratio of curing agent to slurry containing silicone resin is 0.7-0.9:8.8-9), and stir at a speed of 300-400 r / min for 2-4 min at room temperature to obtain the coating slurry based on the silicone resin modified polyurethane.

[0013] (5) The coating slurry is applied to the protected substrate, and it is evenly applied using an applicator, and cured at room temperature for 9-12 hours to obtain a silicone resin modified polyurethane-based intumescent flame retardant and heat-insulating coating.

[0014] Preferably, the polyurethane described in step (1) is MR-326 polyurethane resin.

[0015] Preferably, the purity of the DMF in step (1) and the APP, PER and MEL in step (2) are all higher than 99%.

[0016] Preferably, the expandable graphite described in step (2) has a diameter of about 60-90 μm.

[0017] Preferably, the ammonium polyphosphate (molecular formula: ) is the type for n>1000.

[0018] Preferably, the powdered methylsiloxane resin in step (3) is composed of (CH3-SiO 3 / 2 )x, purchased from WACKER Chemical (China) Co., Ltd., Germany.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) Polyurethane molecular chains contain a large number of carbamate groups (-NHCOO-), which have strong polarity and can form hydrogen bonds with polar groups on the metal surface. In addition, the active isocyanate group (-NCO) can react with moisture or hydroxyl groups on the metal surface to form urea bonds, forming chemical bonds and further enhancing adhesion. This study uses polyurethane as the coating matrix, which can maintain good adhesion with aluminum, titanium alloy, nickel alloy, and steel surfaces at room temperature. Therefore, the new intumescent flame-retardant coating developed in this project has broad application prospects.

[0021] (2) The addition of silicone resin inhibits the "malignant expansion" of expandable graphite. Without affecting the original flame retardant and heat insulating properties of expandable graphite, a thick and dense porous carbon layer is formed, which greatly improves the anti-burning ability of the carbon layer and the anti-burning time is increased to more than 2 hours.

[0022] (3) Due to the introduction of silicone resin, the coating can achieve in-situ high-degree vitrification and ceramicization inside the expandable carbon layer structure under high-temperature flame ablation. Therefore, the expandable flame-retardant coating developed in this project performs very well in terms of condensed phase physical insulation. In the thermal insulation performance test performed in accordance with GB / T12441-2008, the back temperature of the substrate coated with the coating can be reduced to 174°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a curve diagram of the back temperature variation over time of polyurethane-based coating samples with different compositions in the flame retardant and heat insulation performance test (PUIC-EG-SR is a coating prepared according to Example 1; PUIC-EG is a coating prepared according to Example 1 but without adding silicone resin; PUIC is a coating prepared according to Example 1 but without adding expandable graphite and silicone resin);

[0024] Figure 2 The graph is drawn from the data obtained by cone calorimetry analysis of polyurethane-based coating samples with different compositions (PUIC-EG-SR is a coating prepared according to Example 1; PUIC-EG is a coating prepared according to Example 1 but without adding silicone resin; PUIC is a coating prepared according to Example 1 but without adding expandable graphite and silicone resin; (a) heat release rate; (b) total heat release rate; (c) smoke release rate; (d) total smoke release; (e) CO release rate; (f) CO2 release rate);

[0025] Figure 3 are scanning electron microscope photos of the carbon residue surface after expansion of polyurethane-based coatings of different compositions (PUIC-EG-SR is a coating prepared according to Example 1; PUIC-EG is a coating prepared according to Example 1 but without adding silicone resin; PUIC is a coating prepared according to Example 1 but without adding expandable graphite and silicone resin);

[0026] Figure 4 are scanning electron micrographs of the cross-section of carbon residues after expansion of polyurethane-based coatings of different compositions (PUIC-EG-SR is a coating prepared according to Example 1; PUIC-EG is a coating prepared according to Example 1 but without adding silicone resin; PUIC is a coating prepared according to Example 1 but without adding expandable graphite and silicone resin);

[0027] Figure 5 are XRD spectra of polyurethane-based coatings of different compositions at different calcination temperatures (PUIC-EG-SR is a coating prepared according to Example 1; PUIC-EG is a coating prepared according to Example 1 but without adding silicone resin; PUIC is a coating prepared according to Example 1 but without adding expandable graphite and silicone resin);

[0028] Figure 6 is an isothermal adsorption-desorption curve image obtained by N2 adsorption-desorption test of polyurethane-based coatings with different components (PUIC-EG-SR is a coating prepared according to Example 1; PUIC-EG is a coating prepared according to Example 1 but without adding silicone resin; PUIC is a coating prepared according to Example 1 but without adding expandable graphite and silicone resin); DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] A method for preparing a silicone resin modified polyurethane-based expandable flame retardant and heat-insulating coating comprises the following steps:

[0032] (1) Put the polyurethane slurry in a container, then drop N,N-dimethylformamide (DMF) into the container to mix with the polyurethane (the mass ratio of DMF to polyurethane is 0.8:1.8), and mechanically stir at room temperature at a speed of 300 r / min for 10 minutes to prepare the coating matrix slurry.

[0033] (2) Weigh ammonium polyphosphate (APP), pentaerythritol (PER), melamine (MEL), expandable graphite (EG) and the slurry prepared in step (1) in order according to a mass ratio of 3.2:1.2:1.9:2.4:23.1, and place them separately. First, grind APP, PER, and MEL in a mortar, and add them to the slurry together with EG after they are completely ground and uniformly, and mechanically stir them at a speed of 350 r / min at room temperature for 20 minutes to obtain a mixed solution containing a flame retardant system.

[0034] (3) dissolving powdered methyl silicone resin in isopropyl alcohol (IPA) in a certain proportion (the mass ratio of methyl silicone resin to IPA is 2.8:4.8), and mechanically stirring at a speed of 300 r / min at room temperature for 3 h to obtain a transparent and viscous silicone resin sol;

[0035] (4) Add the silicone resin sol in step (3) to the mixed solution in step (2) (the mass ratio of silicone resin sol to mixed solution is 3.2:32.2), and mechanically stir at a speed of 350 r / min at room temperature for 20 minutes to obtain a slurry containing silicone resin. After adding 101C type curing agent (the mass ratio of curing agent to slurry containing silicone resin is 0.7:8.8), stir at a speed of 350 r / min at room temperature for 3 minutes to obtain the silicone resin modified polyurethane-based coating slurry;

[0036] (5) The coating slurry is applied to the protected substrate, evenly applied using an applicator, and cured at room temperature for 12 hours to obtain a silicone resin modified polyurethane based intumescent flame retardant thermal insulation coating.

[0037] Embodiment 2

[0038] A method for preparing a silicone resin modified polyurethane-based expandable flame retardant and heat-insulating coating comprises the following steps:

[0039] (1) Put the polyurethane slurry in a container, then drop N,N-dimethylformamide (DMF) into the container and mix with the polyurethane (the mass ratio of DMF to polyurethane is 0.9:2), and mechanically stir at room temperature at a speed of 280 r / min for 12 minutes to prepare the coating matrix slurry.

[0040] (2) Weigh ammonium polyphosphate (APP), pentaerythritol (PER), melamine (MEL), expandable graphite (EG) and the slurry prepared in step (1) in order according to a mass ratio of 3.3:1.3:2:2.5:23.2, and place them separately. First, grind APP, PER, and MEL in a mortar, and add them to the slurry together with EG after they are completely ground and uniformly mixed, and mechanically stir at a speed of 300 r / min at room temperature for 18 minutes to obtain a mixed solution containing a flame retardant system.

[0041] (3) dissolving powdered methyl silicone resin in isopropyl alcohol (IPA) in a certain proportion (the mass ratio of methyl silicone resin to IPA is 3:5), and mechanically stirring at a speed of 320 r / min at room temperature for 3.2 h to obtain a transparent and viscous silicone resin sol;

[0042] (4) adding the silicone resin sol in step (3) to the mixed solution in step (2) (the mass ratio of silicone resin sol to mixed solution is 3.3:32.3), mechanically stirring at a speed of 320 r / min at room temperature for 18 min to obtain a slurry containing silicone resin. After adding 101C curing agent (the mass ratio of curing agent to slurry containing silicone resin is 0.8:8.9), stirring at a speed of 350 r / min at room temperature for 3.5 min to obtain the silicone resin modified polyurethane-based coating slurry;

[0043] (5) The coating slurry is applied to the protected substrate, evenly applied using an applicator, and cured at room temperature for 10 hours to obtain a silicone resin modified polyurethane based intumescent flame retardant thermal insulation coating.

[0044] Embodiment 3

[0045] A method for preparing a silicone resin modified polyurethane-based expandable flame retardant and heat-insulating coating comprises the following steps:

[0046] (1) Put the polyurethane slurry in a container, then drop N,N-dimethylformamide (DMF) into the container and mix with the polyurethane (the mass ratio of DMF to polyurethane is 1:2.1), and mechanically stir at a speed of 330 r / min at room temperature for 13 minutes to prepare the coating matrix slurry.

[0047] (2) Weigh ammonium polyphosphate (APP), pentaerythritol (PER), melamine (MEL), expandable graphite (EG) and the slurry prepared in step (1) in order according to a mass ratio of 3.4:1.4:2.1:2.6:23.3, and place them separately. First, grind APP, PER, and MEL in a mortar, and add them to the slurry together with EG after they are completely ground and uniformly mixed, and mechanically stir at a speed of 330 r / min at room temperature for 16 minutes to obtain a mixed solution containing a flame retardant system.

[0048] (3) dissolving powdered methyl silicone resin in isopropyl alcohol (IPA) in a certain proportion (the mass ratio of methyl silicone resin to IPA is 3.2:5.2), and mechanically stirring at a speed of 330 r / min at room temperature for 3.5 h to obtain a transparent and viscous silicone resin sol;

[0049] (4) adding the silicone resin sol in step (3) to the mixed solution in step (2) (the mass ratio of silicone resin sol to mixed solution is 3.4:32.4), mechanically stirring at a speed of 290 r / min at room temperature for 16 min to obtain a slurry containing silicone resin. After adding 101C type curing agent (the mass ratio of curing agent to slurry containing silicone resin is 0.9:9), stirring at a speed of 370 r / min at room temperature for 3.6 min to obtain the silicone resin modified polyurethane-based coating slurry;

[0050] (5) The coating slurry is applied to the protected substrate, evenly applied using an applicator, and cured at room temperature for 11 hours to obtain a silicone resin modified polyurethane based intumescent flame retardant thermal insulation coating.

[0051] The polyurethane-based expandable flame-retardant and heat-insulating coating provided by the present invention is modified by silicone resin; on the one hand, the addition of silicone resin suppresses the "malignant expansion" of expandable graphite to form a thick and dense porous carbon layer without affecting the original flame retardant and smoke suppression properties; on the other hand, the addition of silicone resin helps the coating to generate silicon-based glass phase materials inside and on the surface of the expandable carbon layer structure after being heated, thereby improving its ablation resistance, so that the expandable carbon layer can still maintain good integrity under long-term and continuous ablation by high-temperature flames, effectively resist the intrusion of external heat sources, and provide a good thermal protection effect for the coated substrate.

[0052] In order to verify the effect of the above-mentioned method for preparing the silicone resin modified polyurethane-based intumescent flame retardant thermal insulation coating, the inventors conducted the following experiments:

[0053] (1) Thermal insulation performance test: Apply the prepared coating slurry on a Q235 steel plate with a specification of 100mm×100mm×1mm, and use a coater to apply it evenly with a thickness controlled at 1.5mm. After the coating is cured, connect three K-type thermocouples to its back, and use a DC5508U data logger (Pumei, Shenzhen, China) to record the change in the back temperature of the steel plate over time. The heat source used in the experiment is a butane flame spray gun. The flame length during the test is 80mm and the test time is 2h. During the coating test, the curve of the back temperature change over time is shown in the figure below: Figure 1 shown.

[0054] Depend on Figure 1It can be seen that the changes of each curve can be divided into three stages. First, in the rapid heating stage, the temperature suddenly rises due to the direct contact between the coating surface and the flame. From the information in the figure, it can be seen that the temperature rise of sample PUIC in this stage is the most obvious, reaching a maximum temperature of 276°C in 191s. After adding expandable graphite, the time for the back temperature of sample PUIC-EG to reach the peak temperature is gradually delayed to 244s, and the maximum temperature is 244°C. The addition of expandable graphite improves the flame retardancy of the coating. PUIC-EG-SR reaches a maximum temperature of 217°C in 296s, which is 100s later than PUIC, and the temperature is reduced by 21.38%. This shows that the addition of silicone resin helps to further improve the flame retardancy of the coating. Secondly, the temperature drops rapidly in the second stage. This is because the charred structure produced by the violent expansion of the coating when it encounters fire can isolate the heat source from the coating substrate, so that the substrate is no longer in direct contact with the heat source, resulting in a gradual drop in temperature. The third stage is the equilibrium stage, in which the heat insulation of the carbon layer and the heat transfer of the flame are in equilibrium. At 20 minutes, the carbonized layer structure of PUIC was burned through by the high-temperature flame (test termination), which shows that the carbonized structure produced by the expansion of sample PUIC has poor resistance to combustion erosion and cannot provide the necessary thermal protection for the protected substrate in the case of fire. After adding expandable graphite, the anti-burning time of the carbon layer of sample PUIC-EG can be extended to 40 minutes, but after 40 minutes, large cracks appear in the carbon layer (test termination). The addition of silicone resin improves this phenomenon, and the anti-burning time of the carbon layer of sample PUIC-EG-SR can be extended to 2 hours or even longer, which shows that the introduction of silicone resin enhances the anti-combustion erosion ability of the carbonized structure, so that it can still maintain good structural integrity under long-term exposure to flames, thereby resisting the invasion of external heat sources and providing an effective thermal barrier effect. By comparison, PUIC-EG-SR has the best thermal insulation performance, with a final temperature of only 174℃, which is 30.95% lower than PUIC (252℃).

[0055] (2) Cone calorimetry test: First, pour the prepared coating slurry into a mold with a size of 100mm×100mm×4mm and use it for cone calorimetry test after it is cured. This experiment uses Vouch 6180 cone calorimeter tester, and the test is in accordance with standard ISO 5660. The thermal radiation flux during the test is 35kW / m 2 The obtained cone calorimetry test data is shown in the figure below. Figure 2 shown.

[0056] like Figure 2 As shown in Figure 2, after adding silicone resin, the flame retardancy and smoke suppression properties of the coating have been improved accordingly. Figure 2(a) It can be seen that the heat release rate of the coating PUIC-EG-SR is 50.9% lower than that of the traditional APP-PER-MEL system coating PUIC. Figure 2 As shown in (c) and (d), comparing the smoke release rate and total smoke generation of the three coatings, the silicone resin modified coating PUIC-EG-SR is the lowest, with the peak smoke release rate reduced by 93.4% and the total smoke generation reduced by 87.3%. Figure 2 (e) and (f) are the CO generation rate and CO2 generation rate of the three coatings, respectively. The CO generation rate of the coating PUIC-EG-SR is the lowest at 0.00229 g / s, which is 37.6% lower than that of the coating. The CO2 generation rate of the coating PUIC-EG-SR is also the lowest at 0.1009 g / s, which is 58.4% lower than that of the coating.

[0057] In summary, judging from the cone calorimetry test results, the addition of silicone resin effectively improved the flame retardant and smoke suppression properties of the coating.

[0058] (3) Analysis of the surface microstructure of the coating's expandable carbon structure: The microstructure of the residual carbon structure of the coating after the thermal insulation performance test was observed using a scanning electron microscope (Nanosem430, FEI) to understand the improvement of the physical thermal insulation of the condensed phase of the coating by the introduction of silicone resin.

[0059] Figure 3 The electron microscope scanning images of the carbon residues of the three coatings at different magnifications. It can be seen from the scanning images of PUIC at different magnifications that the carbon residue surface of the coating PUIC of the traditional APP-PER-MEL system has been completely broken under long-term flame erosion, and such a carbon layer structure cannot isolate the external heat from the protected substrate. For the coating PUIC-EG with expandable graphite, more "worm-like" structures are formed on the surface of the carbon layer structure, but this "malignant expansion" will provide a path for heat to be transmitted to the substrate, which is specifically manifested as the "worm-like" carbon layer destroying the flat surface of the carbon layer and having more holes. After silicone resin modification, the "worm-like" carbon layer on the carbon layer surface of the coating PUIC-EG-SR is reduced, and the carbon layer surface is smoother, which can effectively improve the thermal insulation capacity of the carbon layer. This shows that the addition of silicone resin helps to improve the integrity of the carbon residue structure under flame ablation.

[0060] (4) Microscopic morphology analysis of the cross-section of the coating’s expansive carbon layer structure:

[0061] Figure 4The electron microscope scanning images of the cross-section of the carbon residue of the three coatings at different magnifications show that the carbon residue of the PUIC coating of the traditional APP-PER-MEL system is mainly composed of loose and irregularly stacked carbonized sheets. This carbon layer has low strength and is easily eroded by flames. By observing the electron microscope images of PUIC-EG at different magnifications, it is found that after adding expandable graphite, the morphology of the PUIC-EG carbon layer has changed. The carbon layer is mainly composed of a "worm-like" structure, which is loosely arranged. There are large pores inside the carbon layer. This is the result of the "malignant expansion" of expandable graphite. The cross-sectional appearance of the carbon residue of the silicone-modified coating PUIC-EG-SR has changed. The "worm-like" structure carbon layer is closely arranged, as shown in the figure under 10um, and smaller pores are formed inside the carbon layer. This shows that the addition of silicone resin helps to improve the strength of the carbon residue structure and promote the formation of pores inside the carbon layer.

[0062] (5) XRD spectra of different coatings at different calcination temperatures: In order to explore the changes in the internal components of the coating during the thermal reaction, the coating was heat treated at room temperature to 1200°C in a tubular furnace. After the treatment, it was analyzed using an XRD tester (D / Max2500v / PC, Rigaku).

[0063] like Figure 5 As shown in the figure, when the temperature rises from RT to 200°C, the three coating components do not react significantly. When the temperature rises to 200-400°C, the main additives APP, PER and MEL all decompose, indicating that this temperature range is the main stage leading to foaming and expansion. Figure 5 As shown in the figure, when the temperature is above 400°C, a huge hump appears in the spectrum of PUIC between 2θ=5-35°, which corresponds to amorphous carbon (low intensity). The amorphous carbon generated by the PUIC coating is the main component. Observing the spectrum of PUIC-EG, after adding expandable graphite, the strong diffraction peak corresponding to graphite covers the amorphous carbon, resulting in changes in the XRD spectrum. This carbon layer has a high degree of crystallinity, thereby improving the flame retardant properties of the material. Observing the spectrum of PUIC-EG-SR, after adding silicone resin modification, SiO2 crystals were found in the spectrum at 400°C. At higher temperatures, the SiO2 crystal peak was masked by the strong diffraction peak of graphite. The formation of SiO2 crystals is beneficial to improving the ablation resistance of the carbon layer.

[0064] (6) Analysis of parameters such as specific surface area and pore size distribution: The residual carbon structure of each coating was tested by N2 adsorption and desorption using ASAP 2460 (Micromeritics, GA, USA). Before the test, each sample was degassed in a helium environment at 150°C for 3 h and then tested.

[0065] from Figure 6It can be seen that the adsorption-desorption curves of PUIC and PUIC-EG samples are similar to those of type II carbon residues. Type II isotherms reflect the typical physical adsorption process on non-porous or macroporous adsorbents. The adsorption-desorption curve of PUIC-EG samples is similar to type IV isotherms, and an adsorption hysteresis loop appears in the middle section, which corresponds to the system where capillary condensation occurs in porous adsorbents. The pore size of PUIC carbon residue is about 1nm, which is almost a non-porous structure. The pore size of PUIC-EG carbon residue is about 40nm, which is a macroporous structure. The pore size of PUIC-EG-SR carbon residue is about 20nm, which is a porous structure.

[0066] The test results show that the total pore volume increases from 0.0022cm 3 / g increases to 0.052cm 3 / g. Correspondingly, the specific surface area of ​​the sample increased from 0.659m 2 / g increased to 2.561m 2 / g. In general, after adding expandable graphite, the carbon layer changes from micropores to macropores, and after adding silicone resin, the carbon layer changes from macropores to mesopores. For porous structures, the smaller the pore size, the larger the specific surface area, and the better the thermal insulation effect. Therefore, adding silicone resin helps to improve the porous carbon residue structure and enhance the thermal insulation effect. In addition, the reduction of pore size will also improve the mechanical properties of the coating to a certain extent.

Claims

1. A method for preparing a silicone resin modified polyurethane-based intumescent flame retardant thermal insulation coating, characterized in that: The preparation method comprises the steps carried out in the following order: (1) Put the polyurethane slurry in a container, then drop N,N-dimethylformamide (DMF) into the container and mix with the polyurethane (the mass ratio of DMF to polyurethane is 0.7-1.1:1.8-2.2), and mechanically stir at room temperature at a speed of 250-350 r / min for 10-15 minutes to prepare the coating matrix slurry. (2) Weigh ammonium polyphosphate (APP), pentaerythritol (PER), melamine (MEL), expandable graphite (EG) and the slurry prepared in step (1) in order according to the mass ratio of 3.2-3.4:1.2-1.4:1.9-2.1:2.4-2.6:23.1-23.3, and place them separately. First, grind APP, PER, and MEL in a mortar, and add them to the slurry together with EG after they are completely ground and uniformly, and mechanically stir them at a speed of 250-350r / min at room temperature for 15-20min to obtain a mixed solution containing an intumescent flame retardant system. (3) dissolving powdered methylsilicone resin in isopropyl alcohol (IPA) in proportion (the mass ratio of methylsilicone resin to IPA is 2.8-3.2:4.8-5.2), and mechanically stirring at room temperature at a speed of 250-350 r / min for 3-4 hours to obtain a transparent and viscous silicone resin sol. (4) Add the silicone resin sol in step (3) to the mixed solution in step (2) (the mass ratio of silicone resin sol to mixed solution is 3.2-3.4:32.2-32.4), and mechanically stir at a speed of 250-350 r / min for 15-20 min at room temperature to obtain a slurry containing silicone resin. Then, add 101C type curing agent (the mass ratio of curing agent to slurry containing silicone resin is 0.7-0.9:8.8-9), and stir at a speed of 300-400 r / min for 2-4 min at room temperature to obtain the coating slurry based on the silicone resin modified polyurethane. (5) The coating slurry is applied to the protected substrate, and it is evenly applied using an applicator, and cured at room temperature for 9-12 hours to obtain a silicone resin modified polyurethane-based intumescent flame retardant and heat-insulating coating.

2. A method for preparing a silicone resin modified polyurethane-based intumescent flame retardant and heat-insulating coating according to claim 1, characterized in that: The polyurethane described in step (1) is MR-326 polyurethane resin.

3. The method for preparing a silicone resin modified polyurethane-based intumescent flame retardant and heat-insulating coating according to claim 1, characterized in that: The purity of DMF described in step (1) and APP, PER and MEL described in step (2) are all higher than 99%.

4. A method for preparing a silicone resin modified polyurethane-based intumescent flame retardant and heat-insulating coating according to claim 1, characterized in that: The expandable graphite described in step (2) has a diameter of about 60-90 μm.

5. The method for preparing a silicone resin modified polyurethane-based intumescent flame retardant and heat-insulating coating according to claim 1, characterized in that: The ammonium polyphosphate (molecular formula: (NH4, H)) described in step (2) n +2P n O 3n+1 ) is the type for n>1000.

6. The method for preparing a silicone resin modified polyurethane-based intumescent flame retardant and heat-insulating coating according to claim 1, characterized in that: The composition of the powdered methylsiloxane resin in step (3) is (CH3-SiO 3 / 2 )x, purchased from WACKER Chemical (China) Co., Ltd., Germany.

Citation Information

Cited By

  • Optical cable belting material with high flame retardance and high resistivity

    CN120904731A